2019
DOI: 10.3389/fnins.2019.00599
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sleep Quality and Internet Addiction Among Female College Students

Abstract: Background: Over 40% of Taiwanese College students experience sleep problems that not only impair their quality of life but also contribute to psychosomatic disorders. Of all the factors affecting the sleep quality, internet surfing is among one of the most prevalent. Female college students are more vulnerable to internet-associated sleep disorders than their male counterparts. Therefore, this study aims to investigate (1) the relationship between internet addiction and sleep quality, and (2) whether signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
81
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 50 publications
14
81
0
2
Order By: Relevance
“…Sleep latency refers to the time it took students to fall asleep, with subjects asked how often they had trouble getting to sleep within 30 minutes. In university students, this parameter is related to internet addiction [ 38 ]. These data, together with recent studies showing that the population increased their use of technology before going to bed during lockdown [ 18 ], explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep latency refers to the time it took students to fall asleep, with subjects asked how often they had trouble getting to sleep within 30 minutes. In university students, this parameter is related to internet addiction [ 38 ]. These data, together with recent studies showing that the population increased their use of technology before going to bed during lockdown [ 18 ], explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Yılmaz, Tanrıkulu and Dikmen [25], it was found that nursing students had a poor sleep quality and a mean score of 6.52 ± 3.17. Lin et al [26] examined the relationship between internet addiction and sleep quality among university students and found that sleep quality was poor. Similarly, Ji and Wang [27] evaluated sleep quality of university students in China and found that the students had poor sleep quality and the PSQI scores above seven.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, one of the greatest changes in the last decade in Nepalese lifestyle is that internet use has increased substantially in more than half of the total population [25]. Possible mechanisms through which internet use may cause obesity include a disrupted sleeping schedule leading to weight gain as well as effects on an individuals' regular food consumption [10,11,37].…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that excessive internet use and internet-based activities, especially during weekends and leisure hours, affect individuals' regular food consumption patterns, standard sleep hours, and sleeping schedules that are associated with weight gain [9][10][11]. One study showed that night-time internet use, especially for video games and complementary day-time sleeping, is significantly associated with increased body mass index (BMI) [12].…”
Section: Introductionmentioning
confidence: 99%